The Mediating Role of Eating Behavior in the Relationship Between Rumination and Sleep Quality in University Students - Shaghayegh Shafiee; Neda Arabsheybani; Sajjad Saadat (Caspian Journal of Neurological Sciences, 2025)
Background: Sleep quality refers to the overall effectiveness and restorative nature of an individual’s sleep experience and is a critical indicator of both physical and mental health. Objectives: The present study aimed to investigate the mediating role of eating behavior in the relationship between rumination and sleep quality in university students. Materials & Methods: The present study was cross-sectional using structural equation modeling. The statistical population included all students of Islamic Azad University, Tehran Research and Sciences Branch, Tehran City, Iran, in 2024. In this study, 250 students were recruited through convenience sampling using an online survey. The research tools included the Pittsburgh sleep quality questionnaire, the ruminative response scale, and the Dutch eating behavior questionnaire (DEBQ). The data were analyzed through structural equation modeling, SPSS, and AMOS software, version 24. Results: The research model has a good fit. Rumination had a significant direct effect on sleep quality (β=0.451), external (β=0.383), restrained (β=-0.309), and emotional (β=0.380) eating behaviors. Also, external (β=0.508), restrained (β=0.220), and emotional (β=0.149) eating behaviors had a direct and significant effect on sleep quality. The indirect effects of rumination on sleep quality through external eating (β=0.194), restrained eating (β=-0.067), and emotional eating (β=0.056) were reported to be significant. Conclusion: Eating behaviors demonstrate both protective and harmful roles in sleep quality. While external and emotional eating intensifies the negative impact of rumination on sleep, restrained eating appears to mitigate it. These findings emphasize the distinct functions of different eating styles in shaping sleep outcomes through rumination.